2015
DOI: 10.1002/pca.2583
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of phenylpropanoids and iridoids in insulin‐sensitising extracts of Leonurus sibiricus L. (Lamiaceae)

Abstract: HPLC-CAD analysis allowed sensitive quantitation of the selected marker compounds in Leonurus sibiricus, thereby providing a reliable tool for its quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The presence of 11 was noteworthy since it is not an ubiquitous compound, especially in the Stachys genus where it has been recognized only in a few species such as S. lavandulifolia [36], S. sieboldii [15], and S. tymphaea [8]. This compound resulted to be a constituent of other systematically related genera such as Leonurus [37,38], Lagochilus [39], and Sideritis [40]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of 11 was noteworthy since it is not an ubiquitous compound, especially in the Stachys genus where it has been recognized only in a few species such as S. lavandulifolia [36], S. sieboldii [15], and S. tymphaea [8]. This compound resulted to be a constituent of other systematically related genera such as Leonurus [37,38], Lagochilus [39], and Sideritis [40]. …”
Section: Discussionmentioning
confidence: 99%
“…From recent studies on iridoid activities, 8-O-acetylharpagide (2) and ajugoside (1) resulted to be useful compounds in the treatment of diabetes mellitus since they were able to stimulate the cellular glucose intake and lower the glucose blood level [38]. Another target of iridoids for the antidiabetic activity is represented by the inhibitory action, verified by docking studies, on glycogen phosphorylase-a [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HepG2 hepatocellular carcinoma cells quercetin was found to mediate autophagy by release of Ca 2+ from intracellular stores [42] and to enhance apoptosis by induction of a positive feedback loop consisting of p53, miR-34a miRNA and SIRT1 [43]. The present study was performed to investigate short and long-term effects of quercetin and rutin on beta-cells [1,2]. While most studies which describe insulinotropic influences of flavonoids on beta-cells focus on short term effects, data on chronic exposure are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was performed to identify LS extract compounds accounting for the observed effects on beta-cell viability, insulin release and electrophysiological behavior. We focused on the flavonoid quercetin and its glycoside rutin, two phytochemicals which could be identified as constituents of LS extracts by HPLC analyses [1,2] and which are known to exert comparable effects in different cell systems.…”
Section: Introductionmentioning
confidence: 99%